Controlled rectifier using single-phase Matrix converter / Rahimi Baharom - Baharom, Rahimi (2009)
In this work basic investigations are carried out on the operation of a proposed single-phase AC-DC converter using single-phase matrix converter (SPMC) topology. Two different categories of operation, namely; a) AC-DC converter including safe commutation strategies to avoid generation of damaging voltage spikes, and b) with input LC filter. This is then extended to operate the SPMC as an advanced AC-DC converter with boost rectifier operation feeding a RC load subjected to active power filter function. The power circuit uses a pair of back-to-back IGBT with diode in series arranged in common emitter mode to realize its required bi-directional operation. Open-loop control was realised using the Pulse Width Modulation (PWM) technique implemented using Peripheral Interface Controller (PIC) at the heart of its control electronics. Basic resistor and inductor loads are used during operation to ascertain the behaviour. A closed-loop control using standard proportional integral control was used to implement active power filter functions to correct the pulsating nature of the input current to almost unity power factor form with low total harmonic distortion (THD) level well below the acceptable limit that was defined in the standards of IEEE 519-1992. This was implemented using both the analogue and digital techniques of control. Wave shaping is facilitated through the use of boost technique that could perform corrections making it continuous, sinusoidal and in phase with the supply voltage. Prior to its practical realization a computer simulation model is developed to investigate the behaviour of the SPMC using MATLAB/Simulink (MLS) incorporating SimPowerSystem and Pspice circuit simulations. An experimental test—rig was then constructed to verify the operation; incorporated with control electronics, gate drives, and power circuits. It is presented that the proposed AC—DC converter using SPMC had been theoretically developed, conceived and successfully realised complete with active power filter function.